Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
[tex]\\\qquad\quad\displaystyle\sf {:}\longrightarrow (y-5)2-(y-3)2=12 [/tex]
[tex]\\\qquad\quad\displaystyle\sf {:}\longrightarrow 2y-10-2y-6=12[/tex]
[tex]\\\qquad\quad\displaystyle\sf {:}\longrightarrow 2y-2y-10-6=12 [/tex]
[tex]\\\qquad\quad\displaystyle\sf {:}\longrightarrow -16=12 [/tex]
[tex]\\\qquad\quad\displaystyle\sf {:}\longrightarrow y's\:value\:is\:undefined [/tex]
Answer:
[tex] {(y - 5)}^{2} - {(y - 3)}^{2} = 12 \\ = ( {y}^{2} - 10y + 25) - ( {y}^{2} - 6y + 9) = 12 \\ = {y}^{2} - 10y+ 25 - {y}^{2} + 6y - 9 = 12 \\ = - 4y + 16 = 12 \\ = - 4y = 12 - 16 \\ = - 4y = - 4 \\ = y = \frac{ - 4}{ - 4} \\ = \boxed{y = 1}[/tex]
y=1 is the right answer.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.